Adaptation and Resilience: Lessons Learned From Implementing a Combination Health and Education Intervention for Adolescent Girls and Young Women in South Africa During the COVID-19 Pandemic - Duby, Zoe; Bunce, Brittany; Fowler, Chantal; Jonas, Kim; Govindasamy, Darshini; Wagner, Colleen; Mangoale, Kgahliso; Ambrose, Anthony; Mathews, Catherine (Frontiers in Health Services, 2022)
The COVID-19 pandemic has been associated with reduced access to health services and worsening health outcomes for HIV and sexual and reproductive health (SRH). Through the analysis of data from an evaluation study of a combination intervention for adolescent girls and young women (AGYW) in South Africa, we sought to examine the way in which implementation and service provision were impacted by the COVID-19 pandemic and related restrictions, describing the adaptation implementers made to respond to this context. The intervention was implemented from 2019 in South African districts identified as high priority, given the high rates of HIV and teenage pregnancy amongst AGYW. The South African government introduced the first COVID-19 lockdown in March 2020. We conducted in-depth interviews with 38 intervention implementers in the period from November 2020 to March 2021. Respondents described various ways in which the COVID-19 pandemic and related restrictions had limited their ability to implement the intervention and provide services as planned. As a result, AGYW intervention beneficiary access to SRH and psychosocial services was disrupted. Implementers described several ways in which they attempted to adapt to the pandemic context, such as offering services remotely or door-to-door. Despite attempts to respond to the context and adapt services, overall COVID-19 negatively affected implementation and service provision, and heightened issues around community acceptability of the programs. Our findings can help to inform efforts to reduce health service disruption, increase health system resilience, and ensure continuous SRH service provision to AGYW in times of pandemics and other crises.